Teacher’s Perception on the Use of Gamification for Students with Learning Disabilities - Ranjanie Karunamoorthy; Mohd Mokhtar Tahar; Ummi Kalthum Mohd Mokhtar (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2020)
Problems with the negative behaviours of special needs students cause special education teachers to experience stress in the classroom. The purpose of this study was to explore the perceptions of special education teachers on the use of ClassDojo application to reduce negative behaviours among students with special needs in learning. This study is based on the Behaviourist theory whereby the relationship between stimulus and response influences the individual learning process. This is a qualitative study that used structured interviews to obtain data from respondents. Interview questions were adapted and modified from Burger's (2015) study. This research question was reviewed and validated by 2 expert lecturers and 2 expert teachers. A total of 2 teachers, and 5 special needs children in Kluang district, Johor were selected as the study sample by means of sampling technique. The findings show that there is a significant change in learning behaviour during the ClassDojo application. The special education teachers feel that the ClassDojo application is very helpful in controlling the classroom while reducing the negative behaviours of the pupils during teaching and learning. Special education teachers also feel that the ClassDojo application creates collaboration and  a positive relationships between teachers and parents to address learning behaviour issues. This study is a reference to future researchers in exploring other gamification applications for learning with special needs children.